The Relationship Between the Work Environment and the Leadership Style of the Head of the Room with Nurse Retention at the Toto Kabila Regional General Hospital, Bone Bolango Regency - Julisty Nur’ain Abdul; Sitti Rahma; Dewi Suryaningsi Hiola (Universitas Muhammadiyah Palu, 2025)
Nurse retention is the process by which nurses are encouraged to stay together with the organization. In addition to organizational components, assignment or job design, awards, career opportunities and relationships between nurses, nurse retention is also influenced by other external factors such as the work environment and the leadership style of the boss. The purpose of the study was to determine the relationship between the work environment and the leadership style of the head of the room with the retention of nurses at the Toto Kabila Regional General Hospital, Bone Bolango Regency. This study is a quantitative research with a cross sectional approach. Sampling was conducted using a purposive sampling technique with a sample of 65 respondents. Data analysis using the fisher exact test. The results showed that there was a relationship between the work environment and nurse retention (p-value = 0.031) and there was no relationship between the head of the room leadership style and nurse retention (p-value = 0.52). In conclusion, the variables of the work environment were related to nurse retention, while the leadership style of the head of the room had no relationship with nurse retention. In addition to a good work environment, external factors related to the hospital also play a role in determining whether or not nurses stay in their jobs. Therefore, it is hoped that hospitals can continue to maintain, improve and improve the existing work facilities and managerial systems in hospitals.